"It's important to know about this" - risk communication and the impacts of chronic wasting disease on indigenous food systems in Western Canada. Issue 123 (September 2021) - Parlee, Brenda; Ahkimnachie, Kevin; Cunningham, Hannah; Jordan, Magdalena; Goddard, Ellen
Abstract: Wildlife diseases, such as Chronic Wasting Disease (CWD) are growing in prevalence in ungulates in western Canada with many questions being asked about the impact on ecosystems and peoples. A collaborative research project involving a university and a regional Indigenous organization was initiated in 2007 to explore how CWD risk is being communicated to Indigenous peoples, how associated risk is being interpreted and the extent to which information about CWD and perceived risk is affecting harvest and food security. Data collected between 2008–2018 with 105 harvesters from 22 northern Alberta communities reporting about hunting in roughly 61 management units (WMU) confirm previous research about the importance of moose, white-tailed deer and mule deer to the diets of Indigenous peoples. Findings affirm the significance of ungulates to the food security of Indigenous peoples in western Canada with over 97 % of respondents reporting their motivation for harvest of moose ( Alces alces), white-tailed deer ( Odocoileus virginianus ) and mule deer ( Odocoileus hemionus ) being food. Insights about risk communication and perception of CWD are also highlighted with the most significant finding being the high level of concern of harvesters in all areas and all years of the study. A second key finding relates to the relationship between information received about CWD which declined from 2008 to 2018 despite significant increases in the number of positive cases of CWD in Alberta. A third key finding is the importance of Indigenous Knowledge; over 97 % of respondents shared indicators of healthy moose and deer which they use to assess animals in hunting. This high degree of confidence in their own knowledge may suggest Indigenous knowledge is a mediator of risk perception (i.e., hunters are confident they can find and harvest a health animal despite the rising number of CWD cases). Although Indigenous right to lands and resources including wildlife harvesting have been little respected in the past, recognition of such rights, as well as Indigenous knowledge, is key to moving forward and developing more collaborative approaches to monitoring and managing the growing threat of CWD and other wildlife disease.